Effect of Electrolyte and Electrode Configuration on Cu‐Catalyzed Nitric Oxide Reduction to Ammonia. Issue 5 (14th January 2022) - Krzywda, Piotr M.; Paradelo Rodríguez, Ainoa; Benes, Nieck E.; Mei, Bastian T.; Mul, Guido
Abstract: Reduction of nitric oxide was investigated using Cu electrodes in acid and neutral pH conditions. Analysis of Cu discs in stagnant electrolyte by Electrochemical Mass Spectrometry (EC‐MS), revealed the favorable formation of ammonia (and hydrogen) in acidic electrolyte, while N2 O and N2 are formed in significant quantities at neutral conditions. Additional performance evaluation of Cu electrodes in hollow fiber geometry, was performed using 10 vol % NO in Ar supplied through the porous electrode structure and off‐line determination of ammonia by 1 H NMR spectroscopy. The pH dependent performance of the Cu hollow fiber is in agreement with EC‐MS data at low gas flow rates, showing the highest ammonia selectivity in acidic conditions. However, at relatively high gas flow rates, almost 90 % faradaic efficiency and a NH3 production rate of 400 μmol h −2 cm −2 were obtained in neutral electrolyte at −0.6 V vs RHE, likely due to enhanced availability of NO at the electrode surface, suppressing the hydrogen evolution reaction. This approach shows conversion of waste NO gas to valuable green fertilizer components is possible. Abstract : Producing green fertilizer components : Efficient supply of nitric oxide to a Cu electrode was achieved by synthesis of a hollow fiber geometry and flow‐through operation. A high faradaic efficiency and production rate of ammonia were achieved by suppression of the hydrogen evolution reaction.